TOURISM POTENTIAL DEVELOPMENT IN THE PERSPECTIVE OF GREEN GOVERNMENT IN BALI PROVINCE - Panji Kusuma Prasetyanto; Dyah Ayu Kusumaningrum (Jurnal Paradigma Multidisipliner (JPM), 2021)
Tourism and income inequality is a phenomena that is interconnected, especially in Indonesia, one of which is the area of Bali, which can be know from the state of the economy seen. Income inequality between southern Bali and northern Bali is striking because of the average income people in the tourism sector. The objective of this paper is to study the role of tourism to poverty alleviation including: 1) to income inequality; 2) to analyze increasing competitiveness; 3) to analyze increased value added; 4) to sustainable development; 5) governance. This study uses qualitative approach using secondary data obtained through in-depth exposure and focus discussions. Research was conducted in BAPPEDA (Badan Pemerintah Daerah).Various attempts have been made to address these issues with government policy through green government. Keywords: tourism, income, government, policy